Ant mimicry in the spider Myrmecotypus iguazu (Araneae: Corinnidae), with notes about myrmecomorphy in spiders - Rubio, Gonzalo Daniel (2013)
We describe the mimetic relationship between the ant-like spider Myrmecotypus iguazu Rubio & Arbino 2009 (Araneae: Corinnidae) and the carpenter ant Camponotus sericeiventris Gue´rin (Hymenoptera: Formicidae), studied in a subtropical rainforest in Iguazu´ National Park, Argentina. The morphological adaptations, aspects of coloration, and behavior responsible for the ant-like appearance in M. iguazu (the mimic) provide strong evidence that its model is C. sericeiventris. Both field observations and field and laboratory experiments suggest that this spider is a Batesian mimic.